Maternal and neonatal outcomes following a proactive peripartum multidisciplinary management protocol for placenta creta spectrum as compared to the urgent delivery. (June 2019) - Stanleigh, Jonathan; Michaeli, Jennia; Armon, Shunit; Khatib, Fayez; Zuckerman, Boris; Shaya, Michael; Ioscovitch, Alexander; Shenfeld, Ofer; Greenblat, Dvora; Farkash, Rivka; Tevet, Ahron; Samueloff, Arnon; et al.
Abstract: Background: Adherent and invasive placenta, termed Placenta Creta Spectrum (PCS), is associated with increased maternal morbidity and mortality. Incidence and risk factors for Placenta Creta are on the rise and call to optimize the obstetric care for this condition. Objectives: We sought to compare maternal and neonatal outcomes between a ProActive Peripartum Multidisciplinary Approach (PAMA) as compared to the urgent management of the Placenta Creta Spectrum patients. Study design: We conducted a single-center prospective observational study between 2005-2016. PCS patients registered with the implementation of a PAMA protocol 2014–2016 epoch(E2) were compared with the pre-PAMA 2005–2013 epoch(E1), managed by urgent team recruitment. The PAMA protocol is grounded on a continuum of care; A. Antenatal: PCS risk assessment based on clinical history and imaging, surgical, anesthesia, urological consults and designation of a dedicated team to be present at planned surgery; B. Delivery: planned at 34–35 weeks, massive transfusion protocol activation, insertion of ureteral catheters, vertical uterine incision, placement of vessel loops on the iliac vessels, avoidance of active placenta delivery, followed by the decision of hysterectomy or uterine repair; C. Post-operative care: intensive care admission. We evaluated maternal and neonatal outcomes. Results: During the study period 158, 438 deliveries were registered in our institution; we identified a total of 72 PCS cases (0.05%): 50(69.4%) in E1 and 22 (30.6%) in E2. Patient characteristics were comparable among epochs. Significantly, patients in E2 vs. E1 had fewer events of massive blood transfusion 36.0% vs. 13.6%, p = 0.05; were transfused less RBC units: median 4 vs. 1.5, p = 0.012, had no transfusion-related respiratory complications and hemorrhage control re-laparotomies. Hysterectomy and hollow visceral injury rates were comparable (72% vs. 63.7%, 26% vs. 22%; respectively). The hysterectomy pathology assessment was available for the majority of the cases in both epochs; percreta diagnosis rate significantly increased in E2. The neonatal outcome was similar among the epochs. Conclusions: Institution of a PAMA protocol for PCS resulted in eliminating the urgent deliveries and in reducing the associated significant hemorrhagic related maternal morbidity, with no increase in the rate of hysterectomy or adverse neonatal outcome.